What drives international gas prices in competitive markets? Four fallacies and a hypothesis - Mike Fulwood (The Oxford Institute for Energy Studies, 2024)
The market for internationally traded gas has now globalized, assisted by the advent of US LNG from the Lower-48. The volume of flexible LNG has increased sharply since 2016 and was instrumental in the diversion of LNG cargoes to Europe, following the loss of Russian pipeline gas in 2022. In a globalized market, the gas price drivers are increasingly complex and simplistic analysis fails to account for these complexities. Simplistic analysis using the "cost stack" and that price always equals marginal cost are no longer relevant, if they ever were. Europe was also never hooked on cheap Russian gas, because it wasn't cheap, and the idea, that some EU politicians and commentators pushed in 2022, that the TTF market was "broken" or not representative, was another fallacy. This paper reviews the move towards a globalized gas market, dispels the fallacies and considers what the real, multi-dimensional, drivers of international gas price are in competitive markets. The value of gas in the market demand centres is the ultimate driver but this value is determined by multiple factors and influences, the importance of which can change, not just from one year to the next but one month to the next or even one day to the next. Where supply is plentiful, relative to demand, as we saw in 2019 and 2020, the short-run marginal cost of supply was a key factor and competition between gas and coal in the power market also important. This changed in 2021, as the world recovered from Covid-19, and even more dramatically in 2022, following the Russian invasion of Ukraine. The market tightened sharply, with demand exceeding supply in Europe, and prices rose well above the long-run marginal cost of supply and a sharp demand response with fuel switching, efficiencies, behavioural changes and even industrial closures all impacting prices. The value of gas rose sharply in the European market and this was transmitted to the rest of the world, especially Asian markets, through the flexible LNG market. The value of gas rose in these markets as well, not because of what was happening in their own markets, but because of the globalized gas and LNG market.
Keywords: 330; fallacies; Gas Prices; globalization; LNG; value of gas